Evaluation of Orexin-A serum levels in karate athletes cohort - Messina, G.; Messina, A.; Monda, V.; Ametta, A.; Sessa, F.; Francavilla, V. C.; Daniele, A.; Monda, M.; Polito, R. (Journal of Human Sport & Exercise, 2020)
The lateral hypothalamus products various neuropeptides, among of these the Orexin-A (hypocretin-1) is a protein that regulates numerous physiological and behavioural processes involving in energy balance and metabolic status, physical activity, blood glucose levels, and food intake. Many data literature reported that the production of Orexin-A increases following regular and structured physical activity. Indeed, it improves energy metabolism and insulin sensitivity, and also modulate energy expenditure and thermogenesis. The higher Orexin-A tone is an endogenous factor that predicts physical activity, improving BMI and the energy expenditure aspect. It is well known that physical activity has positive effects on health and body weight, it improves cognitive performance increasing Orexin-A levels. Given these evidences, the aim of this study is evaluated Orexin-A serum levels in a cohort of karate athletes. Fort these reasons, were recruited 10 young karate athletes and 10 matched non-athletes as control. We evaluated biochemical and anthropometric parameters, and Orexin-A serum levels through ELISA-test. Our results showed that there is a statistical difference between karate athletes and non-athletes in BMI and in biochemical parameters such as glycaemic and lipid profile. Interestingly, Orexin-A serum levels are statistical higher in karate athletes compared to non- athletes. The differences between athlete and non-athletes in this study could be attributed to a better training-related hypothalamic activity in karate athletes. In addition, these evidences indicate that the physical activity has beneficial effects not only on anthropometric and biochemical parameters but also on orexin-A levels, and then on central nervous system.